Does Disciplinary Convention Affect Rhetorical Organization? A Move Analysis of Scopus-Indexed Articles by Indonesian Authors - Depry, Muhammad Imanda; Kurniawan, Eri; Lubis, Arif Husein (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Publication in high-reputation international journals is a necessity for contemporary academics. However, academics face considerable challenges in writing for international publication partly because of failing to meet acceptable rhetorical pattern in accordance with disciplinary convention. This study tries to investigate rhetorical moves in eight Scopus-indexed research articles written by two Indonesian authors from hard science and soft science. The articles were selected based on the authors' status as first authors. To analyze the rhetorical moves, a framework from Maswana, et al. (2015) was adopted and modified. The findings revealed that the authors rhetorically organize their articles mostly in a similar way particularly in the abstract and introduction sections. Similarities were also found in manifesting several steps such as identifying data source and analysis instruments in the methods section, stating and interpreting the results in the findings and discussion section, and highlighting overall results and significance in the conclusion section. However, differences were spotted in the step level particularly in recounting experimental process in the methods section and explaining specific research outcomes in the conclusion section. Those discrepancies might be caused by disciplinary conventions. The results provide a framework and resources for academics striving to write articles for international publications.